Analisis Keuntungan dan Efisiensi Agribisnis Melon (Studi Kasus di Pesantren Manba’ul Ulum Jamanis Kabupaten Tasikmalaya) - Lestari, Auliya Nabilla Noor; Natawidjaja, Ronnie Susman; Rachmawati, Erna; Karyani, Tuti (Universitas Galuh, 2024)
This study aims to determine the added value, profit, and efficiency of the melon business at the Manba'ul Ulum Jamanis Islamic Boarding School. The method used in this study is a qualitative method using primary data through observation, interviews and documentation, and secondary data in the form of scientific journals and literature studies. Based on the research results, it can be concluded that islamic boarding schools get a profit of Rp. 2,334,433.66 from all marketing channels that are passed. The marketing channel that generates the highest profit is modern retail through Asia Plaza and Borma Dakota. Based on the B/C analysis of the melon business at the Manba'ul Ulum Jamanis Islamic Boarding School is efficient with a value of 0.125 with the marketing channel that has the highest efficiency, namely e-commerce of 0.29.